Using REDW Strategy Towards Students’ Reading Comprehension Achievement of the Eighth Grade Students of SMP Negeri 2 Belitang - Vivi, Margarita; Franzhardi, Didi; Retno Kuspiah, Hastuti (ENJEL: English Journal of Education and Literature, 2022)
This thesis is entitled “Using REDW Strategy towards Students’ Reading Comprehension achievement of the Eighth Grade Students of SMP Negeri 2 Belitang”. The problem of the study was limited by teaching reading comprehension achievement by using REDW strategy of the eighth grade students of SMP Negeri 2 Belitang. Th eobjective was find out whether or not REDW strategy is effective to teach students’ reading comprehension achievement of the eighth grade students of SMP Negeri 2 Belitang. The method of the study used experimental menthod which applied one group pretest and posttest. The population of the study was all of th eighth grade students of SMP Negeri 2 Belitang in academic year of 2012/2013, with total number 232 students from eight clasess. In this research, the writer applied random sampling to choose sample class, and the sample class of this study the writer choose VIII2 as the experimental group and VIII4 as the control group with the total students in each class are 29 students. In collecting the data, the writer used written test that was given twice; pretest and posttest, and the analyzing data using t-test. After the writer calculated the students’ scores of pretest and posttest, the writer found the differences of students’ average score in pretest and posttest; 65.75 as pretest and 76.55 as posttest. By using the students’ score obtained from the pretest and posttest in experimental group and control group it was found that the result of independent t-test was 2.60. it is higher than critical value taht is 2.04. this indicated that the null hypothesis (Ho) was refected and alternative hypothesis (Ha) accepted. In other word, REDW strategy was effective to teach students’ reading comprhension achievement of the eighth grade students of SMP Negeri 2 Belitang.